TRINDADE STATION AN ICONIC BUILDING - de Almeida, Diana A. Chumbo; de Albuquerque Amaral, Jorge M. F. (European Scientific Journal, ESJ, 2015)
Deployment of the city, how does it work? By the station of Trindade, an iconic building, in the Oporto City. This article aims to explain the importance of the Void in the architecture, and the relationship between the territory, the building and the Man. We present our analysis and conclusions, to answer our question. We started from existing data, with the concepts, of filled and emptiness, we made several researches, and acquired new data and elements, that were crossed (compared), to support our theory. Throughout the research, we found that the station is considered an iconic building. Has filled gaps in the urban design, â€œEmpty spaceâ€. Once a place without function, and forgotten in the territory, a current problem of the cities. The city "lives" in constantly changing, and through the concepts, of Solidness and Void, we aim to prove that, they contribute to restructure the city. We started the research, with a two-dimensional and three-dimensional analysis, we made photographic records (in the place). At the same time, we reference our research, on the works of Chillida and in the theory of "Terrains Vague" (SolÃ -Morales). When we were crossing the results, we found that the building filled the Void in the Oporto city, and gave it a new use (function and design). So we deduce that, the city and the building â€œlive" as a whole. Deduction, that goes to the meeting of Koolhaas theory, â€œGeneric City" which we add, the metamorphosis process, called by us, has deployment.